An Examination of Preferences for Local Public Sector Outputs - McMillan, Melville L.; Amoako-Tuffour, Joe (The Review of Economics and Statistics, 1988)
Relatively unique data on the costs of public services for local governments in Victoria, Australia, are used to estimate a system of demand equations and to test alternative specifications of the underlying preferences using a translog model. Symmetry conditions are rejected so the data are not consistent with constrained utility maximization. A nonparametric test confirms that result. Conditional on symmetry, tests reject homogeneity and the additivity of preferences and also the separability of personal and property services. Copyright 1988 by MIT Press.